Rhetorical Teaching Strategies for Students with Special Needs at TK Negeri 1 Samarinda - Damayanti, Liliannisa; Wulandari, Maulina Pia; Prasetyo, Bambang Dwi (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The implementation of inclusive education at the kindergarten level still faces significant challenges, especially in the aspect of instructional communication between teachers and students with special needs. This gap shows that conventional teaching strategies have not been able to address the complexity of interactions in inclusive classrooms fully. This study aims to analyze the instructional communication strategies implemented by teachers in Samarinda State Kindergarten 1 using a rhetorical approach. This approach focuses on how teachers build credibility (ethos), touch the emotional side of students (pathos), and convey messages with appropriate logic (logos). This research uses a qualitative approach with a case study method. Data collection techniques include participatory observation, in-depth interviews with teachers and principals, and documentation of learning activities. Data were analyzed thematically to reveal patterns of effective communication in the context of inclusive teaching. The results show that teachers who consciously adopt a rhetorical approach can build stronger communicative relationships, increase student participation, and create a more humane and inclusive learning environment. The conclusion of this study confirms that rhetoric-based teaching strategies are not only relevant but also effective in addressing communication challenges in classrooms with diverse learning needs. The findings recommend the integration of rhetorical approaches in teacher training and inclusive education policy in Indonesia.